Urban growth nexus to land surface temperature in Ghana. Issue 1 (31st December 2022) - Kwofie, Samuel; Nyamekye, Clement; Appiah Boamah, Linda; Owusu Adjei, Frank; Arthur, Richard; Agyapong, Emmanuel
Abstract: Urbanisation in Ghana has been associated with significant effects on the land surface temperature which has its impacts on the natural environment. Conventional literature exhibits that land surface temperature associated with urbanisation have concentrated in the developed world leaving the African terrain unattended to. Hence, its knowledge and implications in Africa and for that matter Ghana is deficient. This study is two-pronged a) examines the relationship between land surface temperature coupled with its spatial patterns (b) examines the surface urban heat island and urban-rural gradient in Greater Accra region of Ghana. Landsat images for 1991, 2002, 2012 and 2020 were used where demarcations for spatial integrity were done. The use of machine learning algorithms were adopted in the land use classification. It was observed that Accra would experience high impervious surface mostly due to rural–urban migration purposely to seek for employment. It was concluded that in order to achieve the Sustainable Development Goals (especially goals 3, 6, 11 and 13) more efforts should be made to improve the conditions in the rural areas in order to curtail the migration drive which does not only put pressure on the social amenities in the urban areas but also exacerbate in the land surface temperature situation.